Pathomorphological changes in patients with Jessner>s lymphocytic infiltrate of skin, reticular erythematous mucinosis and lupus tumidus - P. N. Trophymov; O. V. Antonova; V. R. Khairutdinov; I. E. Belousova; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Jessner's lymphocytic infiltrate of skin, reticular erythematous mucinosis and lupus tumidus are the group of rare, insufficiently explored dermatosis with common clinical and histological features, whose nosology is controversial today. Plasmacytoid dendritic cells play the key role in autoimmune disease induction The target of our study was the analysis of pathomorphological features of lesional skin and the research of plasmacytoid dendritic cells in the skin of patients with Jessner's lymphocytic infiltrate of skin, reticular erythematous mucinosis and lupus tumidus. Material and methods. Histological and indirect immunohistochemistry examination (anti-CD123 antibodies) of lesional skin of 36 patients was held (JLIS - 12, REM - 10, LT - 14) and 10 healthy people. Result. The main pathomorphological changes of skin in all groups were found in dermis: dense perivascular and perifollicular infiltration and deposit of mucin between collagen fibers. Deposits of mucin in papillary dermis were found between patients with JLIS, REM and LT in 10/12 (83%), 7/10 (70%) and 12/14 (86%) of cases, there were no mucin found in skin of healthy people 0/10 (0%) In all dermatosis the distribution of CD123 cells in lesional skin, in immunohistochemistry study, was corresponded clusters model of infiltrate - plasmacytoid DC concentrate in groups around vessels of superficial and profundus networks and perivascular. The comparative analysis of density and localization of perivascular infiltration, number of CD123-cells and their correspondence in dermis perivascular infiltrates didn't reveal statistically significant differences between JLIS, REM and LT. Results. Our results allow us to consider JLIS and LT as identical decease, and REM as similar in clinical-pathomorphological features dermatosis.